KONSTRUKSI POSTMODERN DALAM NOVEL LARUNG - Pujiharto Pujiharto (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2005)
This research study intends to reveal the extent to which Larung (2001), as arecent Indonesian novel, shows postmodern features, especially in its construction,concerning the worlds under erasure and the Chinese box worlds.The theory adopted in the study is that of postmodern fiction by Brian McHale.The method employed is semiotics by Hurshovsky. The theory and method are basedon the assumption that postmodern fiction is ontological in nature. This is differentfrom modern fiction, which is epistemological in nature. According to McHale, theontological nature comprises zones, construction, words, and groundings. Thisstudy investigates, in particular, the construction in Larung.The research findings show that in Larung there are features classified by McHaleinto construction, covering the worlds under erasure and the Chinese box worlds.In the former, Larung explores the features proposed by McHale, namely somethingalways happening, something always existing, excluded middles, forking paths,and a sense of a (non) ending. In the latter Larung also explores features proposedby McHale, namely moving toward infinite regression, trompe-l’oell, strange loops,characters in search of an author, abysmal fictions, and something real. However,in terms of moving toward infinite regression Larung shows opposite features; itdoes not narrate things backward continuously, but it moves backward and forwardto the present. Therefore, Larung can be classified as novel with a postmodernconstruction.